Language and character in Euripides' Electra - Emde Boas, Evert van (Oxford classical monographs, 2017)
This study of Euripides' 'Electra' marries linguistics and literary criticism to provide novel insights into the interpretation of the play. Focusing on characterisation, it demonstrates how the figures are shaped through their use of language, using new means of analysis to argue for a balanced interpretation and challenge prevailing views